Respondent’s Characteristic and Noise Intensity as Predicting Factors of Noise Induced Hearing Loss - Decy Situngkir; Ira Marti Ayu; Laosma Sipahutar (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Sensorineural hearing loss caused by loud noise exposure for a long time is known as the risk ofexperiencing Noise-Induced Hearing Loss. PT. Multi Karya Asia Pacific Raya (PT. MKAPR) is a company that provides products and services to the oil and gas industry in Indonesia. Based on its medical check-up, workshop workers at PT MKAPR have the risk of experiencing Noise-Induced Hearing Loss. The Lodan-9 Workshop area was known to have different noise levels, 88-91 dB in the fabrication, pump and engineering areas, and 90-102 dB in the function test area. The purpose of this study was to identify predicting factors of Noise-Induced Hearing Loss at PT. MKAPR. Method: This study used a case-control design. The population in this study were 26 cases and 48 control. Sample size in this study consisted of 26 cases and 26 control. We used a purposive technique sampling. Data were collected through questionnaire, and then were analyzed by using Chi-Square Test. Result: There were association between noise intensity (P-value: 0.035 OR: 4.714; 95% CI: 1.266-17.561), and work period (P-value: 0.029; OR 5.622; 95% CI: 1.342-23.55) with the incidence of Noise-Induced Hearing Loss. Meanwhile age of workers (P-value: 1; OR: 1.547; 95% CI: 0.336-2.976) and smoking habits (P-value: 0.465; OR: 0.435; 95% CI: 0.096-1.168) have no relationship with the incidence of Noise-Induced Hearing Loss. Conclusion: Noise intensity and work period were predictors of Noise-Induced Hearing Loss on PT.MKAPR’ workers. The longer the workers work in high noise intensity area, the more they are at risk of experiencing Noise-Induced Hearing Loss.Keywords: ear, noise-induced hearing loss, noise, noise intensity